Uma Ferramenta de Autoria para Interação Multimodal em Aplicações NCL 4.0 - Valentim, Pedro Alves; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Digital television has become an increasingly important platform for communication and entertainment, especially with the rise of smart devices and smartphones. Digital TVs now serve as an ideal environment for multimodal interaction experiences. However, programming these experiences presents significant challenges, particularly when dealing with specific programming languages like NCL (Nested Context Language). NCL 4.0, as part of the TV 3.0 Project, offers promising support for multi-user identification and interaction in digital TV applications, aiming to create a more personalized and participatory digital TV environment. Despite its potential, developing NCL 4.0 applications for multimodal interaction remains complex due to the need for understanding its syntax and semantics, as well as creating applications capable of recognizing and responding to voice commands and differentiating viewers. This paper presents an authoring tool designed to simplify the creation of multimodal interaction applications in NCL 4.0. The tool, implemented as a VSCode extension, automates the process of converting remote control interactions into multimodal links, thus reducing the authoring effort. By integrating voice, gesture, and facial expression interactions, the tool allows developers to focus more on enhancing user experience rather than technical implementation details. The paper details the functionalities and implementation of the tool, demonstrating how it can streamline the development process and improve the flexibility and usability of NCL 4.0 applications. Future work includes further testing and exploration of additional interaction modalities to enhance the tool’s adaptability and inclusiveness.